GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 1154680 species occurrences available in GBIF matching the query: TaxonKey: Chenopodiaceae Vent.. The dataset includes 1154680 records from 799 constituent datasets: 403 records from Plant Specimens of Kurashiki Museum of Natural History. 2 records from Herbier du Bénin. 34 records from herbario. 862 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 1 records from Artenvielfalt auf den Elbwiesen (Dessau). 1 records from Naturschutzgebiet Börstig bei Hallstadt. 34 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 100 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Küstenschutzwald. 13 records from MAR - Herbário do Maranhão. 3 records from Plant (MNHM-PL). 1 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 26 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 5 records from Salzwiese Diekskiel. 16 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 803 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 1 records from Schulgelände IGS Kaufungen. 4282 records from Herbarium of The New York Botanical Garden. 56 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 143 records from The System-wide Information Network for Genetic Resources (SINGER). 15 records from CRI - Herbário Pe. Dr. Raulino Reitz. 2 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 25 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 17 records from HAS - Herbário Alarich Rudolf Holger Schultz. 996 records from Marie-Victorin Herbarium (MT). 194 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 5 records from Flora acuática de Querétaro. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 2045 records from NatureServe Network Species Occurrence Data. 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 11306 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 6 records from ArtenFinder. 44 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 54 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 14 records from TEPB - Herbário Graziela Barroso. 45 records from Mongolian Plant (MMNH-PL). 293 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 17 records from Plants of Papua New Guinea. 1 records from Walldorf-Wiesloch: "Natur über den Gleisen". 5 records from Herbario Pontificia Universidad Javeriana. 27 records from ICN - Herbário do Instituto de Ciências Naturais. 3 records from Zukünftiges NSG Höftland/Bockholmwik. 22 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 296 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 23 records from Flora exsiccata Bavarica. 5 records from The Flora of County Clare. 91 records from IICT Herbário LISC. 25 records from Arthropods, Plants, Fungi, and other biodiversity of Costa Rica. 600 records from Kathryn Kalmbach Herbarium. 58365 records from OEH Atlas of NSW Wildlife. 160 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 42 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 212 records from Herbarium Erlangense. 172 records from Herbario de la Universidad de Sevilla, SEV-Historico. 2 records from Herbarium Amazonense. 12 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 71 records from Colección de Herbario. 18 records from HUFU - Herbarium Uberlandense. 10 records from Individual Sightings. 2 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Biologische Station im Kreis Wesel. 3 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 383 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from Schulzentrum "Parc Hosingen". 2483 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 2 records from LBV 100 - Artenvielfalt am Rothsee. 4 records from GEO Biodiversity Day. 9 records from Herbarium Specimens of Bonin and Ryukyu Islands. 5 records from Naturhistorisches Museum Mainz, Botanical Collection. 11 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 103 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 32 records from Herbario Museo de La Salle Bogotá (MLS). 1603 records from The Flora of County Waterford. 113 records from PACA-AGP - Herbarium Anchieta. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 632 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 1 records from Paul-Gerhardt-Schule Dassel. 2 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 12 records from Chenopodieae. 36 records from All observations extracted from the Flora of Northumberland and Durham 1831. 1 records from Bernhardsthal. 15 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 4 records from Botanical collection of the National Museum. 1 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 4 records from PonTaurus collection. 2 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 1 records from Naturschutzgebiet Lüneburger Heide. 168 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 3 records from Plant Systematics Laboratory, Ajou University, Korea. 23 records from New Zealand Biodiversity Recording Network. 3 records from MOSS - Herbário Dárdano de Andrade Lima. 1 records from Naturschutzstation Schmidsfelden. 542 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 1282 records from Specimen Database of Colorado Vascular Plants. 161 records from University of Alberta Vascular Plant Herbarium (ALTA). 1 records from Ackerrain Plönhagen. 9 records from UFG - Herbário da Universidade Federal de Goiás. 1 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 77886 records from Dutch Vegetation Database (LVD). 192 records from Natural History Museum Rotterdam (NL) - Plantae collection. 2 records from EFC - Herbário Escola de Florestas Curitiba. 1 records from Schulhof Gymnasium Hürth Bonnstrasse. 3 records from BioFresh Pond Data. 20 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 2 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 78328 records from SA Flora (BDBSA). 504 records from OAC-BIO Herbarium. 6 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 3 records from Plant observations from Białowieża National Park. 302 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 2 records from Expedition "Schulgelände". 1 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 21 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 2965 records from R. L. McGregor Herbarium Vascular Plants Collection. 106 records from MISS_DC_01MAR2006. 14 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 8167 records from Phanerogamic Botanical Collections (S). 576 records from Aranzadi Zientzi Elkartea. 1 records from Naturnahes Tal in Siena. 1 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 25 records from JPB - Herbário Lauro Pires Xavier. 29 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 1 records from Weinberg Reichersdorf. 93 records from Jordal. 8 records from MfN - Fossil plants (Mesophytic). 184 records from Impetus - Herbarium Hamburgense. 5 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 1 records from Lebensraum Gesamtschule (Langerwehe). 27 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 1 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 1038 records from Herbarium Willing. 4 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3 records from R - Herbário do Museu Nacional. 6 records from Herbier G. Garapin (BOUM). 31 records from Herbarium specimens of Limoges university (LIMO). 717 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 1 records from 3. Tag der Artenvielfalt Hockenheim. 1 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 93 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 25 records from UFMT - Herbário UFMT. 28 records from Instituto de Ciencias Naturales. 377 records from Dataflos. 15 records from Chenopodium. 18 records from Plant specimens of Hokkaido University Museum. 17 records from WII Herbarium Dataset. 1 records from Artenfülle um das Schalkenmehrener Maar. 1 records from Eschlberg Thalhausen. 695 records from SysTax - Botanical Gardens. 131 records from Herbarium Vonderau - FULD. 2 records from Luderbusch. 4667 records from Natural History Museum, Vienna - Herbarium W. 385 records from Herbarium of Jyväskylä University Museum. 81 records from Herbarium BSG Vascular Plants. 1 records from Langes Tannen (Uetersen). 1833 records from Norwegian Species Observation Service. 4 records from Census of the flora of Benin. 382 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 2 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 228 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 4 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 8 records from Miscellaneous Vascular Plants. 1 records from Schlern - (Bozen). 447 records from BioFokus. 3 records from HAMAB - Herbário Amapaense. 6 records from HURB - Herbário do Recôncavo da Bahia. 1 records from HUEG - Herbário da Universidade Estadual de Goiás. 6188 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 222 records from University of California Museum of Paleontology. 18 records from VIC - Herbário da Universidade Federal de Viçosa. 15 records from MfN - Fossil plants (Cenophytic). 208 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1722 records from Vascular Plants, Observations, Oslo (O). 2013 records from UA Herbarium. 4430 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from The Distribution Atlas of Butterflies in Poland. 5 records from HST - Herbário Sérgio Tavares. 9 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 1 records from Biosphäre Bliesgau. 54 records from DAO Herbarium Type Specimens. 43 records from CESJ - Herbário Leopoldo Krieger. 1 records from Dalbek-Schlucht. 3 records from Forster herbarium, Göttingen (GOET). 32 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 4 records from Florística de áreas protegidas en el estado de Durango. 44 records from National vegetation diversity inventory and mapping plan. 98 records from Database of Native Plants in Taiwan. 12291 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 12 records from Paleobotany Division, Yale Peabody Museum. 29542 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 362 records from Michigan State University Herbarium Vascular Plants. 12 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 42 records from Herbier A. Le Grand (BOUM). 1 records from Renaturierung Werse (Innenbereich Beckum). 151 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 16 records from Jardín Botánico Atlántico, Gijón: JBAG. 201 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 4 records from Lustadter Wald .. 51 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 652 records from Jardín Botánico de Córdoba: Herbarium COA. 11 records from HPL - Herbário do Jardim Botânico Plantarum. 1 records from Jardin botanique de Montréal (JBM). 72 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from Balkon (Norderstedt). 6 records from BUND - Dassower See (Lübeck/Dassow). 195 records from Plant (JNHM-PL). 2 records from Gemeindegebiet Weikendorf (Marchfeld). 2 records from Naturschutzgebiet Sistig-Krekeler-Heide. 19 records from Museu de Ciències Naturals de Barcelona: BGJBB. 211 records from Natural History Museum Maastricht (NL) - Herbarium. 2335 records from Plant. 850 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 192 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 5 records from Herbarium togoense. 1157 records from Oklahoma Vascular Plants Database Provider. 397 records from E. C. Smith Herbarium (ACAD). 365 records from H.A. Stephens Herbarium. 1 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 1564 records from Herbarium, Centre for Biodiversity, University of Turku, Finland (TUR). 28 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 730 records from Biologiezentrum Linz. 2535 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 1 records from Trockenrasen Franzigmark (Halle/Saale). 11 records from CPAP - Herbário CPAP. 2 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 87 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 243 records from Geographically tagged INSDC sequences. 9 records from Chenopodium vulvaria. 1 records from Selztal bei Friesenheim. 83 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 34 records from Plant (NSMK-PL). 1 records from SLUI - Herbário Rosa Mochel. 2 records from Dornwanger Moos. 5 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 7 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 71 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 16 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 78 records from Botanical Information System of Geneva. 16 records from Colección Herbario Federico Medem Bogotá - FMB. 10 records from Colección Herbario Universidad Católica de Oriente. 352 records from Polish gene bank – passport data of plants accessions which are important in human life. 5 records from HTSA - Herbário do Trópico Semiárido. 79 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 1 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 454 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 2 records from Wildes Bremer Leben im Park. 43 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 73 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 203 records from Canadian Museum of Nature Herbarium. 8431 records from Belgian IFBL Flora Checklists (1939-1971). 10 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 2 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 11505 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 1 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 2 records from Schloss Fasanerie Eichenzell. 760 records from Herbarium Senckenbergianum Görlitz (GLM). 10 records from Millenium Seedbank (MSB). 235 records from Observational database of Icelandic plants. 2 records from University of British Columbia Botanical Garden Collections (UBCBG). 1723 records from OHN. 1 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 14 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 1394 records from BioGIS - Vascular plants - INPA database. 70 records from Herbarium areqvipense (HUSA). 4 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 38 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 12 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 1 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from Wismar Bucht coast-watching. 3 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 9 records from BioBlitz Barcelona 2010-14. 1503 records from Carnet en Ligne. 2099 records from Botany (UPS). 6 records from Formación del banco de datos del herbario (UCAM). 476 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 8 records from UB - Herbário da Universidade de Brasília. 8 records from National Trust - Heigham Holmes species data held by The National Trust. 99 records from SysTax - Herbaria. 12 records from Inventario Español de Especies Terrestres (MAGRAMA). 5 records from Schatzinsel Wangerooge. 24 records from The Fungal Collection at the Botanische Staatssammlung München. 13 records from Collection du Musée d'Histoire Naturelle de Nice. 8 records from Plant of Folklore (KIDR-PL). 19 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 57 records from Herbario Universidad de Antioquia (HUA). 13 records from LISU Herbario Angola. 2 records from Freiburger GEO-Tag der Artenvielfalt. 38 records from University of Ghana - Ghana Herbarium. 1751 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 71472 records from Botanical Society of the British Isles - Vascular Plants Database. 114 records from Leiner-Herbar Konstanz. 509 records from Herbier de Strasbourg. 6 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 17629 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 1 records from nazza. 965 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Artenvielfalt der Nordsee - Sylt. 2 records from Tullie House Museum - Tullie House Museum. Cumbria Wildlife Trust survey records from 1970 - 2007 of Cumbria Wildlife Sites. Various.. 15 records from ASE - Herbário da Universidade Federal de Sergipe. 51 records from HBGSpermatophyta - Herbarium Hamburgense. 4320 records from Missouri Botanical Garden. 38 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 444 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1857 records from NMNH occurrence DwC-A. 1 records from Plant Specimens collections of the Kyushu UNniversity Museum. 3 records from Bammentaler Duft- und Heilkräutergarten. 1 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 21 records from The Erysiphales Collection at the Botanische Staatssammlung München. 3 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 4 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 8 records from The Vascular Plant Collection at the Herbarium Tubingense. 1 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 2 records from BIOTA Southern Africa - The Collection of Lichens at the Botanische Staatssammlung München. 2 records from Herbario UNAP. 6 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 4 records from West-, Central- and East African Plants Databases. 104 records from Herbario de Universidad de Murcia: MUB. 3 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1 records from SMNS Palaeontological collection - Cretaceous and jurasic invertebrates. 2 records from Inventario nacional de especies vegetales y animales de uso artesanal. 104 records from Institut Botanic de Barcelona, BC-Histórico. 10 records from Banco de Germoplasma del Jardín Botánico Atlántico. 1 records from Langes Tannen. 193 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 4 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 1 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 71 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 51 records from Vascular plants of south-central China. 631 records from Field Museum of Natural History (Botany) Seed Plant Collection. 11 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 2 records from Wälder bei Nordkirchen. 80144 records from Australia's Virtual Herbarium. 4803 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1192 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 229 records from CZE National PGR Inventory. 1 records from Ireland's BioBlitz 2012. 1 records from Wulfsmuehle/Pinnau. 2 records from Schulhof und Anlagensee in Nellingen. 86 records from Kochi Prefectural Makino Botanical Garden. 613 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 5 records from Georgs-Padd (Wangerooge). 49 records from Flora d'Andorra. 3 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 45 records from Plant (KIWE-PL). 201 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 13 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 6 records from Königstetten. 10 records from Plant - Seed (KIDR-PL). 1564 records from Vascular Plant Herbarium, UiB. 8 records from Flora vascular acuática de la cuenca del Río Tamesí. 3 records from SMNS Palaeontological collection - Palaeobotany. 1 records from Unser Schulgelände. 4 records from Plant (JJHA-PL). 70 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 3 records from BÜG. 64 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 1044 records from CONN. 5 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 17181 records from Consortium of California Herbaria. 547 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 2029 records from BioGIS - Vascular plants - A. Danin's point database. 4 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 34 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 1919 records from Royal Botanic Garden Edinburgh Herbarium (E). 14 records from UCBG TAPIR Provider. 1 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Nectar. 18 records from Repatriación de datos del Herbario de Arizona (ARIZ). 203 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 1 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 2 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 2 records from Streuobstwiese Kugelberg (Ulm). 1685 records from Biological and palaeontological collection and observation data MNHNL. 3112 records from Precis Plant Data. 3 records from Chenopodium & Dysphania. 3 records from MEXU/Plantas Vasculares. 11 records from MEXU/Tipos de plantas vasculares. 2 records from Freiburger Tag der Artenvielfalt. 116 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain) (IFN3). 3308 records from United States National Plant Germplasm System Collection. 2 records from Danielsberg (Mölltal, Kärnten). 14 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 1 records from Schulgarten der Volksschule. 1 records from Cuxhavener Küstenheiden. 121 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 64 records from IAC - Herbário do Instituto Agronômico de Campinas. 3 records from New records in vascular plants alien to Kyrgyzstan. 37877 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 117 records from Irish vascular plant data 1999-2009. 13 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 199 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 4 records from Ried und Sand - Artenvielfalt durch Beweidung. 73 records from Swan Coastal Plain Survey. 519 records from Northern Ireland Environment Agency - EHS Species Datasets. 1 records from FCAB - Herbário Friburguense. 6 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 14422 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 91 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 5 records from Chenopodium vulvaria. 4 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 1 records from Triebesbach (Zeulenroda-Triebes). 254 records from University of Vienna, Institute for Botany - Herbarium WU. 125 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 3 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 17 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 6165 records from Vascular Plant Herbarium, Oslo (O). 262 records from Herbarium of Taiwan Forestry Research Institute. 572 records from SANT herbarium vascular plants collection. 294 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1 records from HDJF - Herbário Dendrológico Jeanine Felfili. 1 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 22 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 1 records from Plant (SMNH-PL). 1087 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 161 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from Frauenholz (Holzmaden). 5 records from Herbario de la Universidad Industrial de Santander. 1 records from Töpinger Mischwald. 1 records from GEO-Hauptveranstaltung (Duisburg). 9 records from SPSF - Herbário Dom Bento José Pickel. 14 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 133 records from inatura - Erlebnis Naturschau Dornbirn. 378 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 2 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 520 records from Tiroler Landesmuseum Ferdinandeum. 40 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 5 records from svalbardflora.net. 1 records from Schulgarten Huttenheim (Philippsburg/Baden). 21 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 111 records from BioGIS - Vascular plants - SPNI. 1 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 2 records from Philosophenwald und Wieseckaue in Gießen. 1793 records from The Flora of County Wexford. 14 records from Herbarium Rhoenmuseum Fladungen. 21 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 1 records from Landschaftsschutzgebiet Buchhorst 3. 165 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 550 records from Atlas des plantes vasculaires de Lorraine. 9 records from Plant (NHMK-PL). 10 records from Eppingen und Umgebung. 83 records from Wetland Inventory (NV). 1 records from CVRD - Herbário da Reserva Natural Vale. 28 records from Fieldjournal.org observation database. 5 records from Guadeloupe_Herbier. 1 records from privater Garten. 4 records from The Erysiphales Collection at the University Halle-Wittenberg. 1 records from Tiergarten (Zeitz). 1 records from Warnowufer Groß Klein. 1696 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 794 records from Allan Herbarium (CHR). 2 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 65 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 30 records from Mountain Invasion Research Network (MIREN) survey. 257 records from The digitization of plant specimens of NTU. 3 records from Unna-Mühlhausen, Wiesen. 1362 records from Tromsø Museum, Vascular plants. 145 records from Vascular plant specimens of Akita Prefectural Museum. 33 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 151 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 53267 records from FlorKart - FlorenKartierung Gefaesspflanzen. 5 records from Collection Paleobotanique de l'Universite Paris 6. 4112 records from The Himalayan Uplands Plant database (HUP Version 1). 10 records from Instituto de ciencias naturales. 1456 records from Harvard University Herbaria. 219 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 5 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 7 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 3664 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 90 records from Flora of the Stołowe Mts.. 275 records from Herbario de la Universidad de Granada: GDA. 3479 records from UCJEPS TAPIR Provider. 17 records from Perchtoldsdorfer Heide. 21 records from Lista florística preliminar de Tamaulipas. 25 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 5 records from Nijmegen Natural History Museum (NL) – Herbarium. 2 records from Schulgarten Zinnowwald-Grundschule. 1 records from Artenvielfalt des "Grünen Klassenzimmers". 6 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 865 records from USU-UTC Specimen Database. 262 records from Green Plant Herbarium (TRT). 6 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 4 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 4 records from Scottish Natural Heritage - Standing Waters Database. 10 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 10 records from Type herbarium, Göttingen (GOET). 1 records from BoGART. 18 records from Polish seed gene bank – historical passport data of accessions. 2 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 139 records from Vascular Plants Collection of Sagamihara City Museum. 5 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 476 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 155 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from Diversidad florística y endemismo en la Reserva de la Biósfera El Cielo, Tamaulipas, México. 160 records from Online Atlas of vascular plants 2012-2020. 8 records from MEXU/Colección Histórica. 7 records from Natural Geography In Shore Areas (NaGISA) Dataset. 1 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 49 records from Herbier de Nouvelle-Calédonie. 2 records from Beweidungsprojekt an der Nesse. 4 records from Plant in Baekdu Mountain (KIDR-PL). 1 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 4 records from HVAT - Herbário do Vale do Taquari. 13 records from Plant (GFEI-PL). 134 records from SINGER Coordinator. 19 records from Universität Salzburg. 2 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 69 records from Herbarium (AMNH). 237 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 7007 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 3 records from Vascular Plants Collection of National Museum of Nature and Science. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from Wupperaue bei Kemna (Wuppertal). 80 records from ALCB - Herbário Alexandre Leal Costa. 1 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 764 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 2 records from SMDB - Santa Maria Departamento de Biologia. 30480 records from Artdata. 46 records from Sukkulentensammlung Zürich. 3 records from SJRP - Herbário de São José do Rio Preto. 1497 records from Natural History Museum (London) Collection Specimens. 1370 records from Database Schema for UC Davis [Herbarium Labels]. 99 records from Vascular Herbarium, NMBU. 3 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 1486 records from CIBIO, Alicante:ABH-GBIF. 140 records from University of Lethbridge Herbarium (LEA). 119 records from Vascular plants database of Atugi City Museum. 1219 records from Herbarium Berolinense. 32 records from Southern Cape herbarium. 1 records from FNL e.V.. 4 records from Pontaurus. 3 records from Sudeniederung (Amt Neuhaus). 1 records from Naturpark Kottenforst-Ville 18.6.09. 224 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 1008 records from Nationaal Herbarium Nederland. 3 records from LaBoOb02. 64 records from Chenopodium vulvaria. 1 records from Flora de las Barrancas del Cobre. 88 records from Herbarium of Umeå University (UME). 1 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 12 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 3 records from HUSC - Herbário Unisanta. 71 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 162 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 109 records from Colección Nacional de Paleobotánica - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3 records from Stadt Königs Wusterhausen. 2 records from Real Jardin Botanico, Madrid: MA-Funhist. 4 records from National Trust - Ickworth species data held by The National Trust.. 1 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 1 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 1 records from GEO-Hauptveranstaltung in "Wildtierland". 272 records from Paleobiology Database. 298 records from Biodiversitätsdatenbank des Landes Salzburg. 43 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 17 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 6 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 140 records from BioGIS - Vascular plants - Israeli Gene Bank. 2517 records from naturgucker. 7 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 25 records from Herbarium specimens of CBNA (GAP). 10 records from Factual Database of Native Flora Seeds in Korea. 1 records from SWECO. 3 records from Dorfrand Mauderode. 3 records from NABU-Auerochsenweide. 20 records from Flora of Słowiński National Park, Poland. 2 records from Alien Species in Poland - Plants. 27210 records from Consortium of California Herbaria. 31 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 2 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 54 records from Herbarium (UNA). 82 records from Angiosperm specimens of Iwate Prefectural Museum. 1 records from Feldweg Waldkirchen. 10 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 1 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 1355 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 1 records from Schule Sulzbach (Oberegg). 657 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from Bannwald Burghauser Forst. 98 records from Herbier National de Mauritanie (HNM). 4 records from Korean Ethnobotany Database. 2 records from Gurgltal (Tarrenz). 1510 records from Vascular Plant Herbarium, Trondheim (TRH). 2506 records from Phytochorologie des départements français. 11 records from University of Copenhagen Arboretum. 103 records from Botanical Museum, Copenhagen. Database of type specimens. 544 records from iNaturalist research-grade observations. 9890 records from NSW herbarium collection. 11 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 2 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 66 records from Staffordshire Ecological Record - SER Species-based Surveys. 27 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 49 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 151 records from University of Alberta Museums, Vascular Plant Herbarium. 2 records from Innenstadt Göttingen - Natur Zuhause. 5 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 2 records from Gemeinschaftsgarten Deluxe (Bernburg). 298 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 3 records from Flora vascular del cerro El Zamorano. 2495 records from CAS Botany (BOT). 1 records from Wiese am Waldrand (Gurtweil). 21 records from FUEL - Herbário da Universidade Estadual de Londrina. 1 records from 4. GEO-Tag in Eberbach. 1707 records from Herbario de la Universidad de Sevilla, SEV. 1 records from Kremmer Luch. 358 records from Flore de Franche-Comté. 747 records from Herbarium Senckenbergianum (FR). 11 records from KNWR Herbarium Collection. 2 records from Unser Schulhof - eine Apotheke. 1 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 1 records from Norwegian Biodiversity Information Centre - Other datasets. 21 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 1351 records from Arizona State University Vascular Plant Herbarium. 1 records from Artenvielfalt rund um die Dalbek-Schule. 998 records from Vascular Plant Collection. 1 records from Muehlenbach bei Friesheim. 1 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 46 records from Botany registration database by Danish botanists. 88 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 4 records from Herbarium of University of Białystok - Vascular Plants. 1 records from Gieselbachtal Fulda-Harmerz. 4939 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 491 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 1433 records from Instituto de Botánica Darwinion. 6 records from National System of Protected Areas in Poland - Plants. 49 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 27 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 66 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 1 records from Weidegut Rechab. 6 records from SBT-Living. 4087 records from Vascular Plants, Field notes, Oslo (O). 4 records from HPBR - Herbário Padre Balduino Rambo. 4 records from Garten J. Scherrer (Lachen-Speyerdorf). 1 records from Wattuntersuchung (Cuxhaven). 226 records from Vascular plants collection of Hiratsuka City Museum. 1 records from Wildkräuter. 8524 records from Lund Botanical Museum (LD). 1 records from MEXU/Herbario Los Tuxtlas. 199 records from Utah Valley State College Herbarium. 2 records from Hochschulgelände (Bremen). 15 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 159 records from Nijmegen Natural History Museum (NL) - Herbarium. 713 records from Institut Botanic de Barcelona, BC. 882 records from Herbario del CIBNOR. 1 records from Fuldaaue (Stadtgebiet Fulda). 5 records from Biosphärenpark Wienerwald - Pfaffstätten. 374 records from published_chenopodium_vulvaria_observations. 48327 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 856 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 14 records from National Trust - Sutton Hoo species data held by The National Trust.. 2 records from Butterberg, Dardesheim. 159 records from Herbarium (ICEL). 3081 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from EDIT - ATBI in Gemer area (Slovakia). 27576 records from Observations du Conservatoire botanique national du Bassin parisien.. 2 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 23 records from Botanic Garden of the Finnish Museum of Natural History. 50 records from UPCB - Herbário do Departamento de Botânica. 11 records from Botanical Society of the British Isles - SNH Site Condition Monitoring - Vascular plants (2000-2006). 4 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Umgebung der Grundschule Oderberg. 1192 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 26 records from Base de datos sobre la flora de Durango. 171 records from Staffordshire Ecological Record - SER Site-based Surveys. 1 records from Mainufer. 17013 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from Projekt Dellbrücker Heide. 1 records from Wiese am Unterbecken. 1962 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 8887 records from EURISCO, The European Genetic Resources Search Catalogue. 2 records from invertebratezoology. 82 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 9 records from NINA botanical collection. 9411 records from Flora Atlas N.T.. 315 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Gelände des IVL (Zeckern). 20 records from EAC - Herbário Prisco Bezerra. 383 records from Seed collection – Dead seeds for evaluation and observation purposes. 4 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 6 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 303 records from Louisiana State University Herbarium. 37 records from UEC - Herbário da Universidade Estadual de Campinas. 1 records from schulgarten. 360 records from Nordic Genetic Resources. 466 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Owere Fiddel. 492 records from Botany Division, Yale Peabody Museum. 2 records from Industriegebiet (Kempen). 5 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 219 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 1 records from Isarufer. 1 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 4 records from Naturschutzgebiet Bausenberg. 2337 records from New Mexico Biodiversity Collections Consortium database. 1300 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 49 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 2014 records from IBF Monitoring of Vascular Plants. 1 records from HPAN - Herbário do Pantanal "Vali Joana Pott". 189 records from Herbarium (Åbo Akademi), Centre for Biodiversity, University of Turku (TURA). 4 records from Wangerooge. 2 records from Stadtgebiet (Dannenberg). 3 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 85 records from Herbarium de Geo. B. Hinton, México. 97 records from Royal Botanical Gardens Herbarium. 85 records from Herbaria of the University and ETH Zürich. 322 records from Herbario de la Universidad de Arizona, EUA. 3727 records from BioGIS - Vascular plants - A. Danin's grid database. 121 records from Irish Crop Wild Relative Database. 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from Bayerische Donau - Leipheim. 4905 records from PRECIS. 1 records from Programa de erradicación de los roedores introducidos en la Isla Rasa, Baja California: un plan de restructuración ecológica. 10 records from Gwaii Haanas Marine Plants (OBIS Canada). 4 records from Colección del Herbario PSO de la Universidad de Nariño. 93 records from The AAU Herbarium Database. 1 records from Umgebung der Gesamtschule Hamburg-Winterhude. 9795 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 6 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1624 records from Inventaire National du Patrimoine Naturel (I093) : Flore du Massif Armoricain. 57 records from HRCB - Herbário Rioclarense. 82 records from E.C. Smith Herbarium. 3 records from Pilstingermoos. 10 records from UESC - Herbário Universidade Estadual de Santa Cruz. 1 records from Kiesgruben Wemb. 560 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 36 records from Florística de la reserva de la biósfera de Mapimí. 27 records from Botanical Garden Collection. 3123 records from Israel Nature and Parks Authority. 10 records from Herbario Amazónico Colombiano. 33 records from HVASF - Herbário Vale do São Francisco. 1 records from VFD-H: Rheingau: Pferdeweide Loock. 1 records from Gemeinde Sursee. 1858 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 209 records from Ibaraki Nature Museum, Vascular Plants collection. 277 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 22 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 4 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 3 records from GEO-Hauptveranstaltung (Insel Vilm). 2 records from Herbier CNRST/INERA. 29 records from Botanical Research Intitute of Texas. 1 records from FFH-Gebiet Ahrbachtal. 1 records from Naturgarten Langenholtensen. 7446 records from Australian National Herbarium (CANB). 1 records from Urwald 1 (Bad Waldsee). 50 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 2 records from Küste Wismar-Wendorf bis Hoben. 78 records from Gunma Museum of Natural History, Vascular Plant Specimen. 1 records from Artenvielfalt am Schlern. 13 records from Herbier de la Guyane. 139 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from Schrebergarten Düsseldorf Oberkassel. 9887 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 4 records from Herbier Boreal Confluence (BOUM). 7452 records from FLORIVON. 297 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 18 records from MEXU/Colección de Plantas Acuáticas. 2 records from JOI - Herbário Joinvillea. 3 records from University of Amsterdam (NL) - Páramo pollen reference collection. 3 records from Bergkamen- Bergehalde Großes Holz. 2 records from Ecofact. 14 records from HUEM - Herbário da Universidade Estadual de Maringá. 4 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 3 records from Schanzenanlage Bergham. 5 records from Schatzinsel Norderney. 9 records from DSMZ Collection on Plant Cell Cultures. 21 records from NHT_flora. 2 records from Landschaftspflegehof (Berlin). 1233 records from BSBI tetrad data for Ireland. 4 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 660 records from California State University, Chico. 3 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 3 records from New records in vascular plants alien to Kyrgyzstan. 493 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 2 records from Bayerische Donau - Blindheim Donaubrücke. 118 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 1 records from VSN-Wiese. 1 records from Freiburger Netzwerk Artenvielfalt. 107 records from Vascular plants of Amrum 2007-2008. 296 records from Herbario de la Universidad de Almeria. 5 records from Estonian Nature Observations Database. 1 records from HEPH - Herbário Ezechias Paulo Heringer. 742 records from Colorado State University Herbarium. 1 records from Herbario IES San Isidoro de Sevilla. 1025 records from Vascular Plants, Field notes, Trondheim (TRH). 1 records from Neißetal. 14 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 607 records from Flora-On: occurrence data of the flora of mainland Portugal. 2 records from Plant Specimens of Oiso Municipal Museum. 7 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. 30 records from La etnobiología de los recursos nutritivos en las comunidades Tzeltales en los Altos de Chiapas. 21 records from FURB - Herbário Dr. Roberto Miguel Klein. 2063 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 1 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 704 records from Bernice P. Bishop Museum. 19 records from Colección científica del Museo de Historia Natural Alfredo Dugés.
Keywords: GBIF; biodiversity; species occurrences